XXVII S"ezd KPSS. Doklad Gorbacheva . XXVII S"ezd KPSS. Doklad Gorbacheva . 27th Congress of the Communist Party of the Soviet Union. Gorbachev's Speech . XXVII Съезд КПСС. Доклад Горбачева - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. The first Congress after the deaths of Brezhnev. IU.B. Andropov and K.IA. Chernenko, and the second to last congress in the history of the Communist Party (continued). Featured in the program: Gorbachev, Mikhail Sergeevich (General Secretary of the Central Committee of the CPSU) Первый съезд после смертей Брежнева, Ю. В. Андропова и К. У. Черненко и предпоследний в истории КПСС (продолжение). В программе участвуют: Горбачев, Михаил Сергеевич (Генеральный секретарь ЦК КПСС)